Investigation of the mechanism of trainable recovery capability - Jing, Y.; Yue, J. X.; Zhu, W. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: Can recovery be trained? According to the principle of supercompensation, this study aimed to examine the trainability mechanism of recovery capability and provide some preliminary evidence for further research in the field. Methods 147 adult rats were randomly divided into 21 groups (n=7). After modelling for a week, over a 36 hour interval, the rats were trained with intermittent swimming for 2 weeks. After the training, the rats were sacrificed immediately for the instant groups or after a 36 hour interval for the supercompensation groups. . Data was analyzed using T-test with P<0.05. Results Comparison of BHL, Glu and UA, showed gradual increases in 1 to 5 intervals and decreases after 5×36hours. The increases of the three indicators among 1 to 5 intervals were listed: BHL: 0.8 (1×36h), 1.03 (2×36h), 2.24 (3×36h) 4.03 (4×36h), and 8.12 mmol/L (5×36h); Glu: 1.28, 2.1, 2.33, 5.62, and 7.59 mmol/L; UA: 50.71, 53.14, 65.75, 44.65, and 83.51 umol/L. Liver glycogen in the instant group gradually increased in 1 to 6 intervals and reached a peak at the 6×36hours (55.88±4.72 mg/g, then rapidly decreased. In contrast, the supercompensation group`s glycogen storage in 1 to 5 intervals maintained higher levels, and reached a peak at 5×36h (56.18±3.33 mg/g, and then rapidly decreased. Muscle glycogen in the instant group gradually increased in 1 to 4 intervals, and reached a peak at 4×36hours, and then rapidly decreased to 2.01±1.05mg/g at 5×36hours. Muscle glycogen in the supercompensation group maintained a higher level while increasing at the first five intervals with 5×36hours being a turn-over point (2.28±0.14 mg/g, and then rapidly decreasing. Extent recovery reached its maximal at 4×36hour Discussion./ Conclusions The study shows that the body had a trainable recovery capability. Restoration capacity did not increase without a limit and there was a superimposed process between positive and negative changes. The findings of this study are used to propose a new training theory related to `resuming training capacity`.